Analisis Kualitas Larutan Mikroorganisme Lokal Daun Gamal (Gliricidia sepium) pada Beberapa Waktu Inkubasi - ANAK AGUNG NGURAH GEDE SUWASTIKA; NI WAYAN SRI SUTARI; NI WAYAN MURIANI (Fakultas Pertanian Universitas Udayana, 2015)
Analysis of Local Microorganism Leaf Gamal (Gliricidia Sepium) Solution Quality onthe Fermentation Period. The study aims to determine the quality of local microorganismsolution under the influence of concentration leaves of Gliricidia (Gliricidia sepium) andfermentation period. This research was conducted at the Soil Laboratory, Faculty ofAgriculture, UdayanaUniversity. The design of this research used a randomized block designfactorial pattern of two factors. The first factor was the concentration of Gliricidia leavesconsisted of 0, 100, 300 g, and the second factor was the fermentation period, consists of 1,2,and 3 weeks. Results of statistical analysis showed a highly significant interaction betweenthe concentration factor and fermentation period of Gliricidia leaves the parameters observed.Concentration of 30% (300 g) Gliricidia leaves with a two-week fermentation period has thebest effect on the quality of the biological properties of microorganisms local solution with atotal population of bacteria (9.5 x 107 SPK mL-1) and total fungus (1.9 x 106 SPK mL-1),while the best quality chemical properties of the solution of local microorganisms present in aconcentration of 30% (300 g) gliricidia leaves with a three-week fermentation period with thecontent of total-N (1.59%), pH (6.03), and organic-C (3.35%). Concentration of 30% (300 g)Gliricidia leaves with fermentation period of two weeks, it can be used as a biologicalfertilizer and a concentration of 30% (300 g) Gliricidia leaves with a three-week fermentationperiod, could be used as organic manure.